Place naming in Aceh: The genesis and generic patterns of toponyms in Banda Aceh and Greater Aceh - Aziz, Zulfadli A.; Dewi, Cut; Amalina, Zahria (Universitas Syiah Kuala, 2023)
Studies conducted on documenting toponymic histories and issues of place name taxonomy and etymology in the Acehnese language are few to begin with. As names of villages in Aceh suggest, it indicates that many indigenous place names in the province seem to be redundant and possibly rooted from landscape formations. This study investigates the role of geographical and environmental as well as migration possibilities on their toponymy by using the descriptive method. The data were obtained from Acehnese village names in Banda Aceh and Greater Aceh areas, and observation and in-depth interviews were also used as instruments. The data were analyzed using the model proposed by Miles et al. (2014). The results of this study demonstrate the history and etymology of similar names of villages in Greater Aceh and Banda Aceh areas. However, those names are not related to the migration of people. In general, place naming in Aceh was based on the genesis of the naming and the generic pattern. The former was associated with the specific object or entity, the historical reasons and use of specific-word oriented, whereas the latter was mainly succeeding word-forming elements that followed different patterns of lexicon combinations and loan-words. This study shows that toponyms consist of a multi-facetted structure, which entails different features according to situations.